Flavonol-rich dark cocoa significantly decreases plasma endothelin-1 and improves cognition in urban children - Calderon-Garciduenas, Lilian; Mora-Tiscareño, Antonieta; Franco-Lira, Maricela; Cross, Janet V.; Engle, Randall; Gómez-Garza, Gilberto; Jewells, Valerie; Weili, Lin; Medina-Cortina, Humberto; Solorio, Edelmira; Chao, Chih-kai; Zhu, Hongtu; et al. (Frontiers in Pharmacology, 2013)
Air pollution exposures are linked to systemic inflammation, cardiovascular and respiratory morbidity and mortality, neuroinflammation and neuropathology in young urbanites. In particular, most Mexico City Metropolitan Area (MCMA) children exhibit subtle cognitive deficits, and neuropathology studies show 40% of them exhibiting frontal tau hyperphosphorylation and 51% amyloid-β diffuse plaques (compared to 0% in low pollution control children). We assessed whether a short cocoa intervention can be effective in decreasing plasma endothelin 1 (ET-1) and/or inflammatory mediators in MCMA children. Thirty g of dark cocoa with 680 mg of total flavonols were given daily for 10.11± 3.4 days (range 9 to 24 days) to 18 children (10.55yrs, SD =1.45; 11F/7M). Key metabolite ratios in frontal white matter and in hippocampus pre and during cocoa intervention were quantified by magnetic resonance spectroscopy. ET-1 significantly decreased after cocoa treatment (p=0.0002). Fifteen children (83%) showed a marginally significant individual improvement in one or both of the applied simple short memory tasks. Endothelial dysfunction is a key feature of exposure to particulate matter and decreased endothelin-1 bioavailability is likely useful for brain function in the context of air pollution. Our findings suggest that cocoa interventions may be critical for early implementation of neuroprotection of highly exposed urban children. Multi-domain nutraceutical interventions could limit the risk for endothelial dysfunction, cerebral hypoperfusion, neuroinflammation, cognitive deficits, structural volumetric detrimental brain effects, and the early development of the neuropathological hallmarks of Alzheimer’s and Parkinson’s diseases.